2021
DOI: 10.1051/e3sconf/202126501020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fire on plant biodiversity in the semideserts of Central Kazakhstan

Abstract: The dynamics of species richness and diversity indices in pyrogenic successions of sagebrush and perennial saltwort communities in Central Kazakhstan were analyzed. The biodiversity of such communities during the initial years after fires was higher than that in unburnt phytocenoses. However, values of biodiversity parameters significantly decreased 27-31 years after fires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In North America, similar formations dominated by sagebrush ( Artemisia tridentate ) have long recovery times (>100 years) following fire disturbance (Bukowski & Baker, 2013). In Kazakhstan, where fire recurrence periods in semi‐deserts are shorter (10–20 years, Lednev et al, 2021), dwarf shrubs dominated by less woody sagebrush such as Artemisia terrae‐albae recolonize within 8–16 years following a fire event (Lednev et al, 2021). The recolonization period for saltwort Salsola arbusculiformis communities which exhibit a more pronounced aboveground woodiness and form a higher and denser canopy is longer (30 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, similar formations dominated by sagebrush ( Artemisia tridentate ) have long recovery times (>100 years) following fire disturbance (Bukowski & Baker, 2013). In Kazakhstan, where fire recurrence periods in semi‐deserts are shorter (10–20 years, Lednev et al, 2021), dwarf shrubs dominated by less woody sagebrush such as Artemisia terrae‐albae recolonize within 8–16 years following a fire event (Lednev et al, 2021). The recolonization period for saltwort Salsola arbusculiformis communities which exhibit a more pronounced aboveground woodiness and form a higher and denser canopy is longer (30 years).…”
Section: Discussionmentioning
confidence: 99%
“…The recolonization period for saltwort Salsola arbusculiformis communities which exhibit a more pronounced aboveground woodiness and form a higher and denser canopy is longer (30 years). In the years after a fire event, plant biodiversity in Kazakh semi‐deserts can be higher due to the removal of mature, dominant woody dwarf shrubs, which opens up the site for herbaceous species, especially ruderals emerging from the soil seed bank and fire‐resistant tussock‐forming grasses (Lednev et al, 2021). Altogether, fires in Kazakh semi‐deserts where woody dwarf shrubs are predominant, can lead to at least for one or two decades of more open and herbaceous (steppe‐like) vegetation structures.…”
Section: Discussionmentioning
confidence: 99%
“…Any fluctuations in the species composition of early flowering plants are reflected in the economic component of the economy of Central Kazakhstan. When analyzing the literature, it was found that there are few studies on the biodiversity of useful plants of Central Kazakhstan (Lednev, 2021;Pozdnyakova et al, 2022aPozdnyakova et al, , 2022b. The purpose of our study is to establish the species composition of early flowering plant species in the territory of Central Kazakhstan (Ulytau mountains), to rank plants by ecological groups and the degree of prevalence.…”
Section: Introductionmentioning
confidence: 99%